A study on the Friction Stir Welded Non-ferrous Alloy. (November 2020) - Xu, Anlian
Abstract: Friction stir welding (FSW), which is a new-type solid state welding technology, has been successfully used in aluminum alloys, magnesium alloys and coppers. To study the properties of friction stir welded zinc-based non-ferrous alloys, Zn-0.5Cu alloy plates were butt welded by FSW. The results show that Zn-0.5Cu alloy plates with 5 thickness can be successfully welded by FSW. The joint efficiency of weld joint can reach over 95 % at appropriate weld process parameters.